إمدادات النص الخرافي في بناء الحكاية الشعبية - حكاية سكّرة أنموذجا - عبد العزيز, بوشلالق; هجيرة, عزيزي (جامعة الوادي - University of Eloued, 2021)
الحكاية الشعبية بنصوصها المنطلقة من واقع الفرد، وبأنواعها المختلفة وغنى موضوعاتها جعلها تعدّ من أبرز الأشكال التعبيرية الشعبية، التي حملت تقاليد وأعراف المجتمعات وثقافاتهم وعقائدهم، وعبرت عنهم بصورة حيّة عبر الزمن، مستلهمة نصّها من واقع التجارب الإنسانية ومحملة بالعديد من المزايا الأسطورية، التي اغتنت بها نصوصها المحكية والمتداولة بين المجتمعات ومختلف الثقافات. رغم ما حدث من تقسيمات وتأصيل لنصوص الحكي التراثي، إلا أنّ الحكاية الشّعبية بقيت في نصوصها معتمدة على الجانب الأسطوري الموظّف داخل بعض النصوص، التي تقرب واقعيتها من جهة، وبخرافيتها من جهة أخرى، لأنّها منحت نصّ الحكاية تشويقا سرديا وغرابة مستحبة استلطفها الراوي وتقبلها المتلقي. Abstract : Sucra fairy tale as an example : folk tale texts, geners,enrichment of its topics based on person’s reality, that makes it one of the aspects the popular culture, it carried traditions, cultures and belifs of societies the folk tale also explicated the humane society with an alive form through eras also its texts based on the human experiments,it contains plenty of legendary advantages that riched its narrated and trended among societies and different cultures. Although the folk tale was diverted and its origine shape was changed by time,it remined depending on the fictitious aspect that used within some of texts which are submitted its fact and fiction that gives the folk tale excitable and enjoyable narration.
The Aspects Of The Fictitious Role In The Folk Tale Amodel Of The Story Of Sucra
Keywords: حكاية شعبية ـــ خرافة ـــ سكّرة ـــ رموز سحرية; folk tale - fairy tale - sucra - magic symbols